Upaya Notaris Dalam Menjaga Kerahasiaan Akta Pada Kantor Notaris Sri Wahyono, S.H., M.H., M.Kn - Kusumawati, Ervina Dewi (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
Notaries, in carrying out their duties, have an obligation to keep confidential everything they produce and all information obtained under oath, unless otherwise specified by law in accordance with Article 16(1)(f) of Law No. 02 of 2014 concerning amendments to Law No. 30 of 2004 concerning the Position of Notary. Based on this background, the author is interested in writing a paper entitled ‘The Role of Notary Office Administrative Staff in Maintaining the Confidentiality of Deeds at the Notary Office of Sri Wahyono, S.H., M.H., M.Kn’ and the research question in this study is how Notary Sri Wahyono, S.H., M.H., M.Kn maintains the confidentiality of the contents of deeds. This type of research was conducted using a sociological juridical research method. In essence, notary staff will also become witnesses in deeds and know everything related to the deed. In addition to keeping the contents of the deed confidential, they must also keep the client's statements in the preparation of the deed confidential.